2016
DOI: 10.1177/0038040716680271
|View full text |Cite
|
Sign up to set email alerts
|

(How) Does Obesity Harm Academic Performance? Stratification at the Intersection of Race, Sex, and Body Size in Elementary and High School

Abstract: In this study I hypothesize a larger penalty of obesity on teacher-assessed academic performance for white girls in English, where femininity is privileged, than in math, where stereotypical femininity is perceived to be a detriment. This pattern of associations would be expected if obesity largely influences academic performance through social pathways such as discrimination and stigma. In the Fragile Families and Child Wellbeing Study (~age 9) and the National Longitudinal Study of Youth 1997 (~age 18), I fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 75 publications
1
20
0
Order By: Relevance
“…Lifestyle and diets of children from urban areas make it sufficiently more risky to be overweight compared to children living in deprived rural environments [ 5 ]. Another challenging issue related to overnutrition is poor school performance of the students in their academic score [ 6 ]. Many studies emphasized the positive relationship between obesity and poor school performance [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle and diets of children from urban areas make it sufficiently more risky to be overweight compared to children living in deprived rural environments [ 5 ]. Another challenging issue related to overnutrition is poor school performance of the students in their academic score [ 6 ]. Many studies emphasized the positive relationship between obesity and poor school performance [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In low-and middle-income countries, previous systematic reviews indicated that the prevalence of obesity ranged from 2.3% up to 12% [1], and the rate of overweight and obesity was found to reach 22% in the university students aged 18 to 25 years [4]. There is ample evidence to show that being overweight and obese affected academic productivity and social relationships in young people [5,6]. This problem also increases the risk of cardiovascular disease, diabetes, and metabolic disorders, as well as impaired respiratory functions in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Timed reading assignments or tests may be challenging for students with a learning disability. Other research on health and education suggests that students with health impairments or disabilities face challenges in educational institutions not because of their health limitations but because of structural inequality embedded within educational institutional practices that favors “healthy” students (Branigan 2017; Crosnoe 2007; Shifrer et al 2013). For example, equally academically prepared and cognitively performing students with a learning disability are less likely to take advanced courses in high school than their peers without a disability (Shifrer et al 2013).…”
Section: Postsecondary Barriers To College Completionmentioning
confidence: 99%
“…For example, equally academically prepared and cognitively performing students with a learning disability are less likely to take advanced courses in high school than their peers without a disability (Shifrer et al 2013). Research has also found a link between education and obesity, but gaps are wider in courses with more subjective grading policies, suggesting that obesity is related to academic performance through teachers’ perceptions of students rather than through health limitations (Branigan 2017; Crosnoe 2007). In this light, we examine if equally academically prepared students with a disability have lower rates of bachelor’s degree completion than students without disabilities and examine the features of their postsecondary education that contribute to these gaps.…”
Section: Postsecondary Barriers To College Completionmentioning
confidence: 99%